AB0316 Is there a need to relook at the cut offs of rheumatoid factor in indian population ? - Vasdev, V. (Annals of the rheumatic diseases, 2018)
BackgroundPopulation specific cut offs of titers of Rheumatoid Factor (RF) in diagnosis of Rheumatoid arthritis (RA) and the role of anti citrullinated peptide antibiodies (ACPA) remains unknown.ObjectivesTo define cut offs for RF titres in diagnosis of RA in Indian populationMethodsRF titers of consecutive adult RA patients fulfilling ACR 1987 as well as ACR/EULAR 2010 criteria were compared with healthy normal and diseased non RA controls encountered in the rheumatology OPD of a tertiary care Armed forces Hospital using ROC-AUC analysis. Reclassification of disease phenotype as seropositive and seronegative RA using various the cutoffs was looked into and corresponding Anti-CCP titers in the subset of patients with RA was analysed.ResultsOverall 589 cases of RA (range: 18–69 years; 29.9% Females) were compared with age and sex matched 192 non RA and 51 controls. Mean (+-SE) RF titers in RA cases was 107.7 IU/L (+- 6.17) while that in non RA disease cases was 29.3 IU/L (+- 6.08) and normal healthy controls 14.7 IU/L(0.43). ROC analysis revealed a cutoff titer of 20.3 IU/L (AUC 0.705 (95% CI:0.66–0.74)) with the best combination of sensitivity and specificity for a diagnosis of RA from non RA and healthy controls. With the currently used cut offs of 60 IU/L in our centre as well as high titre RF as per ACR/EULAR 2010 criteria, subjects were seropositive in 286/589 (48.5%) cases. Cutoffs of 40 IU/L and 20 IU/L led to a label of seropositivity in 322 (54.7%) and 396 (67.2%) cases respectively. Simultaneous Anti-CCP was done in 480 (81.4%) cases: 363 (75.6%) of these were positive. Using a cutoff of 60 IU/L as seropositive RA, anti CCP positivity was noted in 246/286 (86%) cases while with a cutoff of 40 IU/L and 20 IU/L it was 278/322 (86.3%) and 334/396 (84.3%) respectively. The RF titers in 117 anti-CCP negative cases was >20,>40 and>60 IU/L in 62 (52.9%), 44 (37.6%) and 40 (34.1%) cases respectively.ConclusionsFor this cohort of Indian population, a cut off of 20 IU/L of RF titers has the best performance for a diagnosis of RA with an additional 18.7% cases labelled as seropositive as against the current ACR cutoffs. Anti CCP positivity also no substantially changed by using this lower cutoff. There is a need to reevaluate the population specific RF titers in conjunction with anti- CCP in Indian population.Disclosure of InterestNone declared